Expanding the default forms in the lexicon: the sound masculine plural inflection - Bassil M. Mashaqbeh, Sabri S.Y. Al-Shboul, Wael Zuraiq, Moh’D Al-omari, Anas Huneety, (Opción)
This paper investigates the applicability of the plural masculine suffix /-i:n/ as a default inflection marker to nouns that have an irregular inflection which is not the suffix /-i:n/. The data taken from Jordanian Arabic (JA) show that the notion canonical root has a substantial role in the emergence of such a default inflection. The findings show that there is a tendency for the suffix /-i:n/ to be the marking default as an apparent form among others in JA despite the fact that they fall outside the ubiquitous regularity domain. These results provide supporting evidence to the notion of multiple default system observed in JA in addition to the Sound Feminine Plural marker with /a:t/ . Finally, these findings conform to the symbolic accounts that rely upon computational mechanisms for the emergence of the default patterns